RIWAYAT HIPERTENSI DENGAN PENYAKIT JANTUNG PADA PASIEN YANG PERNAH TERPAPAR COVID 19 - Riris Andriati; Beti Rianti; Rita Dwi Pratiwi (Edu Masda Journal, 2022)
The increase in the number of Covid-19 cases occurred so quickly. Indonesia is one of the countries affected by Covid-19 with data on 228,993 confirmed cases of Covid-19 from March 2, 2020 to September 16, 2020 with the addition of 3,963 new cases, 9,100 deaths (CFR 4.0%), recovered cases 164,101 (71.2%) and 55,792 cases under treatment 24.4%. The objective of study was to determine whether there is a relationship between a history of hypertension and heart disease in patients who have been exposed to Covid 19 in the South Tangerang area. The research method in this research is quantitative research, a cross sectional design, with a sample of 57 respondents. From the results of the study, the average respondent with a history of hypertension and a history of heart disease was around 41-50 years old as many as 23 people (40,4%) with an average value of 2,70 and a standard deviation of 0,91. Meanwhile, the average respondent who had been exposed to Covid with a history of heart disease and hypertension was 29 men. The results of statistical tests obtained p-value 0.015, so there is a relationship between a history of hypertension and heart disease in patients who have been exposed to Covid-19 in the South Tangerang area. Suggestions of this study are expected that educational institutions can improve and determine various educational programs that can disseminate information about Covid-19, especially for people who have a history of heart disease and hypertension. So that the number of Covid-19 exposures does not increase.ABSTRAKPenambahan jumlah kasus Covid-19 terjadi begitu cepat. Indonesia salah satu negara yang terkena dampak Covid-19 dengan jumlah data kasus terkonfirmasi Covid-19 228.993 dari 2 Maret 2020 sampai dengan per 16 September 2020 dengan penambahan kasus 3.963 kasus baru, 9100 kasus meninggal (CFR 4,0%), kasus sembuh 164.101 (71,2%) dan 55.792 kasus dalam perawatan 24,4%. Tujuan penelitian ini adalah untuk Mengetahui  Hubungan Antara Riwayat Hipertensi Dan Penyakit Jantung Pada Pasien Yang Pernah Terpapar Covid 19 di Wilayah Tangerang Selatan. Metode penelitian dalam penelitian ini adalah penelitian kuantitatif, desain cross sectional dengan sampel sebanyak 57 responden. Dari hasil penelitian diperoleh responden dengan riwayat hipertensi dan riwayat penyakit jantung berumur sekitar 41 – 50 tahun sebanyak 23 orang (40,4%) dengan nilai rata-rata 2,70 dan standar deviasi 0,91. Sedangkan sebagian besar responden yang pernah terpapar Covid dengan riwayat penyakit jantung dan hipertensi berjenis kelamin laki-laki sebanyak 29 orang. Hasil uji statistik diperoleh nilai p-value 0,015 artinya ada hubungan antara riwayat hipertensi dengan penyakit jantung pada pasien yang pernah terpapar Covid-19 di wilayah Tangerang Selatan, diharapkan penelitian ini dapat dijadikan sebagai pedoman oleh perawat dalam memberikan pendidikan kesehatan kepada pasien yang terpapar Covid 19 dengan riwayat penyakit hipertensi dan penyakit jantung.